Anisotropic reinforcement of epoxy-based nanocomposites with aligned magnetite–sepiolite hybrid nanofiller. (20th May 2015) - Marins, Jéssica Alves; Mija, Alice; Pin, Jean-Mathieu; Giulieri, Françoise; Soares, Bluma Guenther; Sbirrazzuoli, Nicolas; Lançon, Pascal; Bossis, Georges
Abstract: Magnetic sepiolite fiber (m-SEP) was successfully prepared by chemical coupling of aminosilane-functionalized sepiolite with epoxysilane-functionalized magnetite, as confirmed by Fourier Transform Infrared Spectroscopy and Transmission Electron Microscopy. This hybrid material was magnetically aligned into an epoxy resin under the action of a relatively weak magnetic field and the resulting oriented dispersion was cured with a polyether amine. The addition of m-SEP increased the flexural modulus of the epoxy nanocomposites and the alignment in the longitudinal direction resulted in an additional reinforcement of the epoxy network, mainly for system containing 10 wt% of m-SEP. These results confirm the anisotropic reinforcing effect of the aligned magnetic sepiolite fibers.